Chemometrics-assisted determination of amiloride and triamterene in biological fluids with overlapped peaks and unknown interferences. (July 2015) - Hu, Yong; Wu, Hai-Long; Yin, Xiao-Li; Gu, Hui-Wen; Kang, Chao; Xiang, Shou-Xia; Xia, Hui; Yu, Ru-Qin
Background: Amiloride (AMI) and triamterene (TRI) are both potassium-saving diuretics, which are ordinarily used as doping to enhance the performance of athletes in sports. For the similar structures and complex matrices existence, chromatography and extraction are commonly employed to realize the determination of AMI and TRI in biological fluids, which are very time-consuming and laborious.Results: A novel method is presented to simultaneous interference-free determination of AMI and TRI in complex biological fluids samples using excitation–emission matrix fluorescence coupled with second-order calibration method based on alternating normalization-weight error algorithm.Conclusion: The proposed method can obtain accurate qualitative and quantitative information of the analytes, even in the presence of the interference from complex biological fluids, which requires few prior purification and separation procedures.